Euklidischer Zusammenhang der Art von Cartan des metrischen Linienelementraumes - Bliznikas, V. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Близникас. Евклидова связность картановского типа в метрическом пространстве линейных элементов V. Bliznikas. Kartano tipo euklidinis sąryšis metrinėje tiesinių elementų erdvėje